2015
DOI: 10.1186/s12885-015-1654-6
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative platelet-lymphocyte ratio is superior to neutrophil-lymphocyte ratio as a prognostic factor for soft-tissue sarcoma

Abstract: BackgroundInflammation can promote tumor growth, invasion, angiogenesis and even metastasis. Inflammatory markers have been identified as prognostic indicators in various malignances. This study compared the usefulness of platelet-lymphocyte ratio (PLR) with that of neutrophil-lymphocyte ratio (NLR) for predicting outcomes of patients who underwent radical resection for soft tissue sarcoma (STS).MethodsWe included 222 STS patients in this retrospective study. Kaplan-Meier curves and multivariate Cox proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 58 publications
1
51
3
2
Order By: Relevance
“…The reason may be that SPTP involving this location is more likely to result in sinistral portal hypertension presenting with a decreased platelet count . Several studies have shown that elevated PLR was superior to NLR as a prognostic indicator for many malignancies such as breast cancer, soft‐tissue sarcoma, and colorectal carcinoma . We were unable to demonstrate the value of PLR in predicting clinical outcomes of SPTP, probably due to the small sample size.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The reason may be that SPTP involving this location is more likely to result in sinistral portal hypertension presenting with a decreased platelet count . Several studies have shown that elevated PLR was superior to NLR as a prognostic indicator for many malignancies such as breast cancer, soft‐tissue sarcoma, and colorectal carcinoma . We were unable to demonstrate the value of PLR in predicting clinical outcomes of SPTP, probably due to the small sample size.…”
Section: Discussionmentioning
confidence: 67%
“…28 Several studies have shown that elevated PLR was superior to NLR as a prognostic indicator for many malignancies such as breast cancer, soft-tissue sarcoma, and colorectal carcinoma. [29][30][31] We were unable to demonstrate the value of PLR in predicting clinical outcomes of SPTP, probably due to the small sample size. Indeed, PLR has not been shown as a predictive marker for IPMN-associated malignancy either.…”
Section: Inflammatory Markers and Rfs After Surgical Resectionmentioning
confidence: 83%
“…While some factors, for instance high tumor grade and inadequate surgical resection are established as prognostic parameters associated with poor outcome in soft tissue sarcomas (STS), the significance of new prognostic factors for survival such as preoperative laboratory parameters has become a recent focus in STS research. Markers of systemic inflammation (elevated CRP, neutrophil/lymphocyte ratio) and pre‐treatment anemia have been shown to predict poor outcome in STS patients . Nevertheless, larger STS cohort studies suggest that differences in biological behavior may exist between sarcoma histotypes .…”
mentioning
confidence: 99%
“…Markers of systemic inflammation (elevated CRP, neutrophil/lymphocyte ratio) and pretreatment anemia have been shown to predict poor outcome in STS patients. [13][14][15][16] Nevertheless, larger STS cohort studies suggest that differences in biological behavior may exist between sarcoma histotypes. 17 Recently it has been shown, that surgical margins are not predictive of local recurrence and survival in high grade myxofibrosarcoma.…”
mentioning
confidence: 99%
“…Several studies have reported that altered perioperative immune function (lymphopenia, elevated platelet/lymphocyte ratio) is associated with poor cancer survival. 25,36 Our study found that celecoxib prevented thrombocytosis (an acutephase response), lymphopenia, and hence an elevation of the platelet/lymphocyte ratio during the early perioperative period. Of interest for future study is whether celecoxib preserves lymphocyte subpopulations (e.g.…”
Section: Discussionmentioning
confidence: 67%